Assessing Capture Risks in the Regulatory Mechanism: Insights from Kenya's Regulation of Professionals in the Construction Labour Market. (December 2022) - K'Akumu, O. A.
The article draws academic attention to capture risks in the regulatory statutes that may lead to capture by regulators. It takes a practical outlook of Kenya for empirical demonstration of the statute-based capture risks. The article uses the Regulatory Impact Assessment (RIA) framework to identify the risk factors in the regulatory environment for professions involved in real estate development, that is, architects, engineers and quantity surveyors. The OECD Reference Checklist for Regulatory Decision-making is used as a reference point in identifying risk analysis as a candidate of inclusion in the checklist for purposes of improvement in regulatory outcomes. Document analysis is used to make observations on the statutes and generate data for qualitative analysis and interpretation. Capture risks are identified in terms of composition of regulatory boards that include powerful public servants. Exclusion of relevant stakeholders in the regulation of professions, inclusion of extraprofessional regulations and uncontrolled legislative powers are other sources of risk of regulatory capture. The article gives central focus to the capture by regulators. Existing regulatory capture literature predominantly consider regulatory capture by private or special interest groups.